PERANCANGAN ALAT BANTU INDIKATOR KUALITAS TANAH DENGAN PARAMETER RESISTIVITAS TANAH DAN PH TANAH UNTUK TANAMAN PADI - Wahyudianto, Dariska Kukuh; Rahmat, Gheschik Safi’ur; Masrur, Moch.; Permana, Rosy Indra; Abidin, Luqi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Farmers need to know land quality before planting padi because land quality will affect the quality of padi. Unfortunately, farmers do not have accurate indicator to examine the quality of land. They usually use their feeling or knowledge generated from their ancestor. This problem has initiated the current study to propose a tool that could indicate the quality of land using land resistivity parameter and land pH. To examine resistivity, Tris-Compatible pH sensor was used. The main feature of this tool is it could identify land resistivity, land pH, land quality, and recommend fertilization accurately. The tool has been proven to be able to detect land quality indicator as it could measure land resistivity and pH. The tools is believed to be easy to use as it does not require specific procedure in the measuring process with water tolerate level of 0% to 50%.